Effect of Descemet Membrane Endothelial Keratoplasty on Color Vision in Patients With Fuchs Dystrophy. Issue 8 (August 2016) - Price, David A.; Price, Marianne O.; Lopez, Amanda; Price, Francis W.
Abstract : Purpose: To assess changes in color discernment after Descemet membrane endothelial keratoplasty (DMEK) in patients with Fuchs endothelial corneal dystrophy (FECD). Methods: In this prospective, single-center study, the study group was composed of 26 patients with FECD, aged 46 to 85 years, who underwent DMEK as a single surgical procedure; 24 (92%) had pseudophakic and 2 (8%) had phakic eyes. The patients completed a computerized Farnsworth–Munsell 100-hue color vision test before and 1 month after DMEK. A control group of 14 subjects, aged 57 to 85 years, was tested 1 month after cataract surgery. Results: The median number of errors made by patients who had undergone DMEK on the color vision test improved from 64 (range 24–124) before surgery to 48 (range 10–120) after surgery ( P = 0.0053). The post-DMEK scores in the 24 patients with pseudophakic eyes (median = 48, range = 10–120) were comparable to those of an age-matched control group of patients with cataract without corneal abnormalities (median = 53, range = 4–104, P = 0.88). The improvement in color vision was not correlated with the amount of improvement in best corrected visual acuity (r = −0.02, P = 0.91) or with the reduction in central pachymetry (r = −0.08, P = 0.71) after DMEK. Conclusions: Consistent with spontaneous comments from some patients with FECD that colors appear more vivid after DMEK, a comparison of pre- and postoperative color vision scores showed that color discernment usually improved after DMEK (81%). The lack of correlation between color vision improvement and pachymetry reduction leads us to hypothesize that color vision improvement may relate to removal of the guttae associated with FECD.